'People like me don't do well at school': The roles of identity compatibility and school context in explaining the socioeconomic attainment gap. (1st March 2022) - Easterbrook, Matthew J.; Nieuwenhuis, Marlon; Fox, Kerry J.; Harris, Peter R.; Banerjee, Robin
Abstract : Background: School students who are eligible for reduced or free school meals (FSM) – an indicator of economic disadvantage – have lower academic attainment than their peers. Aims: We investigated whether identity compatibility – the perceived compatibility between one's social identities and the stereotype of a high‐achieving student – contributes to this socioeconomic attainment gap, and whether the association between socioeconomic status and identity compatibility is moderated by school context. Sample: Our sample was 4, 629 students aged 15–16 years old across 29 schools in England. Method: We assessed students' perceptions of identity compatibility via self‐report questionnaires 8 months prior to them taking national, standardized exams. Results: Multilevel regression analyses revealed a negative indirect effect from eligibility for FSM to exam results via identity compatibility. These effects existed even while accounting for students' gender and language status, other psychological variables known to predict academic attainment, and their previous exam results. Furthermore, school context moderated the relationship between FSM eligibility and identity compatibility. In line with the identities in context model of educational inequalities, there was a significant negative association between FSM and identity compatibility only for students attending schools in which there was previously a relatively large socioeconomic attainment gap. Conclusions: Our results demonstrate the importance of social psychological variables in explaining educational inequalities, and of the local educational context in determining the educational experience of students from lower socioeconomic status backgrounds.